Efficacy and toxicity of methotrexate (MTX) monotherapy versus MTX combination therapy with non-biological disease-modifying antirheumatic drugs in rheumatoid arthritis: A systematic review and meta-analysis - W. Katchamart (2018)
Objective: To evaluate the efficacy and toxicity of methotrexate (MTX) monotherapy compared with MTX combination with non-biological disease-modifying anti-rheumatic drugs (DMARDs) in adults with rheumatoid arthritis. Method: A systematic review of randomised trials comparing MTX alone and in combination with other nonbiological DMARDs was carried out. Trials were identified in Medline, EMBASE, the Cochrane Library and ACR/ EULAR meeting abstracts. Primary outcomes were withdrawals for adverse events or lack of efficacy. Results: A total of 19 trials (2025 patients) from 6938 citations were grouped by the type of patients randomised. Trials in DMARD naive patients showed no significant advantage of the MTX combination versus monotherapy; withdrawals for lack of efficacy or toxicity were similar in both groups (relative risk (RR) = 1.16; 95% CI 0.70 to 1.93). Trials in MTX or non-MTX DMARD inadequate responder patients also showed no difference in withdrawal rates between the MTX combo versus mono groups (RR = 0.86; 95% CI 0.49 to 1.51 and RR = 0.75; 95% CI 0.41 to 1.35), but in one study the specific combination of MTX with sulfasalazine and hydroxychloroquine showed a better efficacy/toxicity ratio than MTX alone with RR = 0.3 (95% CI 0.14 to 0.65). Adding leflunomide to MTX non-responders improved efficacy but increased the risk of gastrointestinal side effects and liver toxicity. Withdrawals for toxicity were most significant with ciclosporin and azathioprine combinations. Conclusion: In DMARD naive patients the balance of efficacy/toxicity favours MTX monotherapy. In DMARD inadequate responders the evidence is inconclusive. Trials are needed that compare currently used MTX doses and combination therapies.